Fabrication and characterization of biomimetic reverse osmosis membrane for brackish water desalination - Ng, Chiann Yi (Nanyang Technological University, 2021)
In the 1960s, the thin-film composite (TFC) membrane was invented and it has since prevailed the reverse osmosis (RO) desalination industry. Thereafter, membrane researchers have continuously attempted to enhance the productivity of the TFC-RO membrane. One of the novel methods is by incorporating synthetic water nanochannels into the polyamide (PA) active layer of RO membranes to form biomimetic membranes, which is inspired by the incorporation of aquaporins into bio-assisted membranes. In this work, we incorporated 1,2-Dioleoyl-sn-glycerol-3-phosphocholine (DOPC) liposomes which contained peptide-appended synthetic water channels, (pR)-pillar(5)arenes (pRPH) into the PA active layer of a TFC membrane to synthesize the pRPH-based biomimetic membrane (pRPH-BM). On top of that, Triethylamine (TEA), (1S)-(+)-10-Camphorsulfonic acid (CSA) and Dimethyl sulfoxide (DMSO) were added as aqueous additives in a bid to further enhance the performance of the pRPH-BM. As a result, we achieved ~30% increment in water flux (from ~52.44 L/m2 h to ~67.2 L/m2 h), most probably attributed to the presence of the pRPH-liposomes and another ~26% increment in water flux (from ~67.2 L/m2 h to ~84.83 L/m2 h) by means of additives, both achievable with uncompromised selectivity when compared against the control TFC membrane. The pRPH nanochannels are believed to provide a preferred passage for water molecules to diffuse through the PA active layer quickly with lower hydraulic resistance as well as a shorter diffusion distance. In addition, the additives are postulated to contribute greatly to the enhancement of the water flux of pRPH-BM because they resulted in a PA active layer which is thinner, smoother, less cross-linked and more hydrophilic.